Percepción de los estudiantes de la maestría de cuidados paliativos de una Universidad privada,sobre la eutanasia en Bogota, Colombia (2022)
Euthanasia is the process of hastening the death of a person with an incurable disease to prevent their suffering (1). There are 7 countries that so far have an acceptance of euthanasia. In Latin America, the only country that has currently legalized euthanasia is Colombia, in Chile and Peru progress has been made on the subject, but there are still no regulations in force, however, there are known barriers that prevent the exercise of this right correct In Colombia, people who present delays in the approval of said intervention, in addition to initiating judicial and criminal proceedings where the patient and his family are forced to carry out procedures with insurers and the State. Palliative care is based on respecting human life, providing care and treatment to improve the quality of life regarding the suffering and discomfort of the disease suffered by the person, this implies pain relief, symptom control, psychological and spiritual well-being, but in none of the cases is euthanasia adopted as an intervention to end the suffering of the patient. Therefore, this research has as a general objective, to describe the perception of the students of the master's degree in palliative care of a private university, about Euthanasia in Bogotá, Colombia. Which used the descriptive qualitative method, which consists of inquiring about the perception of students in the face of euthanasia, delving into their points of view, interpretations and meaning, likewise it is intended to describe the perception of students, reference to euthanasia for collect information in a reliable and accurate way, this in order to contribute and expand the knowledge gap that Colombia presents in the face of euthanasia and contribute to professionals in the health area.